Sintomas depressivos em fatores associados em pessoas idosas - Torella, Danieli Cristina Pasqualotto (2025)
Depressive symptoms are common among older adults and can negatively impact their quality of life and long-term health. This study aimed to analyze the prevalence of depressive symptoms and associated factors among elderly individuals in a municipality with "rururban" characteristics in southern Brazil. Depressive symptoms are common among elderly people and can negatively impact their quality of life and long-term health. Therefore, the present study aimed to analyze the prevalence of depressive symptoms and associated factors among elderly individuals from a municipality with rural-urban characteristics in the South of Brazil. Methodology: This is a cross-sectional study conducted with elderly residents of the municipality of Coxilha, in the state of Rio Grande do Sul, Brazil. The study is part of the "Census of Life and Health Conditions of the Elderly in the Municipality of Coxilha-RS". Data collection was carried out using a standardized, pre-coded questionnaire, addressing demographic, social, and health data. To identify depressive symptoms, the Geriatric Depression Scale (GDS-15) was used. A total of 438 elderly individuals were evaluated. Furthermore, to better understand the quantitative results, an exploratory qualitative study was conducted with a subgroup of elderly individuals who had responded to the questionnaire. Semi-structured interviews were conducted with 10 participants, aged 65 to 74 years, intentionally selected, all presenting depressive symptoms, with preserved mobility, and able to respond without assistance. The interviews were conducted individually, either at the Basic Health Unit or at the participants' homes. The interview recordings were transcribed and analyzed using Content Analysis as proposed by Bardin. Results: The prevalence of depressive symptoms was 20.8% among the elderly participants. Depressive symptoms were associated with objective health aspects, such as negative selfperception of health, as well as conditions related to malnutrition or risk of malnutrition. In the qualitative study, reports indicated that depressive symptoms were often linked to the loss of loved ones, family conflicts, and social isolation. Non-communicable chronic diseases and physical limitations affected the participants' daily activities and overall well-being. Although the elderly individuals were using psychotropic drugs, comprehensive healthcare, especially in rural areas, was considered insufficient. Conclusion: The results of this study indicate that the prevalence of depressive symptoms is closely associated with factors such as the loss of loved ones, family conflicts, social isolation, and health conditions such as chronic diseases and physical limitations. The implementation of coping strategies, such as social participation, social support, spirituality, and physical exercise, proved to be relevant for reducing depressive symptoms. Based on the observed objective and subjective health aspects, it is urgent to implement integrated and effective measures to combat depression in the elderly population, especially in rural areas.